SOCIAL AND COMMUNICATION CULTURE AS AN INTEGRAL PART OF PROFESSIONAL DEVELOPMENT - Shabunina , Viktoriia; Tur , Oksana (Collection of scientific papers «ΛΌГOΣ», 2024)
The article deals with the concept of social and communication culture, which is one of the main characteristics of a modern person, since it plays a fundamental role in the general cultural and professional development of a personality. The main components in the structure of communication culture are named, its functions are characterised. It is proved that communication culture is an important component of the professional culture of a future specialist. The factors influencing its formation are analysed. The indicators of a high level of formation of the communicative culture of a personality are determined.